The effect of different methods and solvents on the extraction of polyphenols in ginger (Zingibier officinale) - Sharif, Mohd. Faez; Bennet, Muhammad Taha (2015)
Food ingredients derived from plants are a rich source of polyphenols. In recent times, polyphenols have become popular for their therapeutic properties as antioxidants. 6-gingerol, the main bioactive phenolic compound in Zingiber officinale, is well known for its free radical scavenging capabilities in treating multiple ailments. The most common method for extracting polyphenols from plant materials is through the use of solvents. The extraction of polyphenols from plant matrix is largely dependent on the type of solvent used and the extraction method employed. However, due to the complexity of plant chemistry there is no obvious choice in solvent or extraction method. In this study we made use of three different solvents; acetone, ethanol, and methanol. Variations of two different methods were used. The reflux was run for 30 minutes at 95 ℃ and maceration was done at room temperature for 8 hours. Between the different methods, maceration extracts generally showed better TPC, 6-gingerol content and antioxidant activity. Ethanol was significantly the best extracting solvent due to its higher polarity index. While the maceration ethanol extracts significantly had the highest TPC and 6-gingerol content, its antioxidant activity was not significantly different from the ethanol reflux extracts. A significantly positive correlation was determined between TPC and antioxidant activity, with reflux extracts having a better correlation than the maceration extracts. A significant positive correlation was also drawn between TPC and 6-gingerol content.